Assessment of deformation in bridge bearing areas using measurements and welding simulation. (July 2022) - Kollár, D.; Kövesdi, B.; Völgyi, I.; Biró, I.
Abstract: Deformations of bottom flanges in the vicinity of bridge bearings, i.e., in bearing areas, due to manufacturing and loading can result in serious problems in service life and damages in bridge superstructures and structural bearings coming from nonuniform stress distribution. The paper focuses on the out-of-flatness measurement of bearing areas using Coordinate Measuring Machine (CMM) in typical steel and composite bridges having box and open cross-sections. Advanced manufacturing simulations are also carried out in addition to site measurements to analyse imperfections due to welding during assembly and strengthening of a typical bridge superstructure. A qualitative comparison is made with measurement results showing that the magnitudes of simulated and measured distortions are in good agreement. Results are evaluated in accordance with the permitted total deformation limit in EN 1337–2 recommended for spherical structural bearings. The current study uses a novel approach in the field of bridge engineering; the analogy of Abbott-Firestone curve is applied for describing the deformed shape and evaluating the extent of defects in the contact area since the magnitude of out-of-flatness imperfection is not inevitably sufficient for classifying the surfaces. Based on the obtained results it is demonstrated that using additional transverse bearing stiffeners for strengthening the superstructure can result in large distortions. Even the magnitude of out-of-flatness due to welding of transverse bearing stiffeners can exceed the permitted limit resulting in nonuniform stress distribution in the sliding elements affecting wear resistance and service life of spherical structural bearings. Highlights: Imperfections of bottom flanges in bridge superstructures are investigated. Comprehensive CMM measurements and qualitative welding simulations are carried out. Results are evaluated in accordance with permitted deformation limit in EN 1337–2. Abbott-Firestone curves are used to describe the deformed shape of contact areas. Influence of retrofitting on out-of-flatness is highlighted.